Pengaruh Parameter Sistem Transmisi Tenaga Listrik pada Saluran Transmisi Pendek - Fitri, Sulistianingsih Nur; Azis, Fatmawati (Joule (Journal of Electrical Engineering), 2024)
The Effect of Electrical Power Transmission Network Parameters on Short Transmission Line. The transmission system is one of the components of the electrical power operation system where its reliability is crucial. An electrical transmission system has parameters that influence its reliability to function effectively as part of the power system. These parameters include resistance (R), inductance (L), and capacitance (C). This study involves simulations using distribution and transmission trainers to understand the effects of these parameters on the transmission channel. There are three types of electrical transmission channel models based on their lengths. This research focuses on simulating a short 3-phase transmission channel. In the simulation of the short transmission system, two types of simulations were conducted: one with variations in RL load and another with variations in RL load and C load compensation. The results of the first experiment showed that the larger the value of the load L, the higher the value of the receiver voltage (VR) and the higher the value of the receiver side power (PR). In the second experiment, it showed that the larger the value of the load C, the higher the source voltage (VS) and the receiver voltage (VR). Meanwhile, the value of the source current (IS), receiver current (IR), and receiver power (PR) decreased. Additionally, the values of the sending current and the receiving current tend to be the same because the equation stating that the sending current is equal to the receiving current applies. This is due to the variation in the values of the RLC load used. Through the simulation carried out, several data points were obtained that help to understand the relationship between voltage and current, such as load impedance (ZLoad), line impedance (ZLine), voltage regulation (VR), reactive power (Q), apparent power (S), transmitted power (PS), power loss (PLoss), and power transmission efficiency (Ŋ).